Training in Learning Strategies for Proletarian Adolescents - Winda, Tan; Solaiman, Yugiantie; Wattimena, Tonny (SERVIRE: Jurnal Pengabdian Kepada Masyarakat, 2021)
Community service activities have the aim of improving the quality of learning for youth at Pademangan, North Jakarta in terms of learning strategies, namely the Problem Based Learning (PBL) strategy (problem based learning). While the form of service carried out is an effective learning strategy for proletarian adolescents. The result of community service activities is that the understanding and ability of proletarian adolescents about learning strategies for proletarian adolescents can be improved by providing training, so that the knowledge and professionalism of teachers can increase success in learning subjects